Corporate Culture and Transformational Leadership on Corporate Sustainable Performance Meadiated of Digital Transformation - Andy Ihza Mahendra; Muhammad Imam Muttaqijn; Dudung Hadiwijaya (International Journal of Business Economics (IJBE), 2024)
Purpose – This study aims to examine and analyze the influence of corporate culture and transformational leadership on sustainable corporate performance mediated by digital transformation.Methodology — This research is quantitative in nature, with exogenous variables of corporate culture and transformational leadership, intervening variables of digital transformation, and endogenous variables of corporate sustainable performance. The unit of analysis is 80 samples of employee respondents who work in airport service support companies. Data analysis in this study used Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software.Findings — The company's digital transformation process can mediate the influence of corporate culture and transformational leadership in building sustainable company performance in the context of managing airport support services companies.Originality/Novelty –The new finding from this research is that digital transformation can mediate the influence of corporate culture and transformational leadership in building sustainable company performance. Testing the role of digital transformation in airport service support companies is considered new and has never been done before.Implications – The results of this research provide theoretical and practical benefits in building sustainable company performance mediated by digital transformation processes in the strategic domain.